Convalescent plasma therapy in B-cell-depleted and B-cell sufficient patients with life-threatening COVID-19 – A case series. (December 2021) - Erber, Johanna; Wiessner, Johannes R.; Huberle, Christina; Schneider, Jochen; Mijočević, Hrvoje; von Bomhard, Doris; Luppa, Peter; Schmid, Roland M.; Rasch, Sebastian; Lahmer, Tobias
Abstract: Objective: To investigate the effect of convalescent plasma therapy (CPT) on clinical courses of B-cell-sufficient and B-cell-depleted patients with life-threatening COVID-19. Patients and Methods: In this case series, we retrospectively analysed clinical, laboratory and cardiopulmonary parameters of six patients with life-threatening COVID-19 receiving convalescent plasma (CP) as rescue therapy between April 11, 2020 to October 10, 2020. Clinical and laboratory parameters before and after transfusion were compared in two B-cell-depleted patients and four B-cell sufficient patients (control group). Results: Both B-cell-depleted patients cleared SARS-CoV-2 virus and survived, while all other patients died within 14 days from intervention despite maximal therapeutic efforts. D-dimer levels increased in both cohorts subsequent to CPT. In control patients, mean Interleukin-6 increased and platelet levels decreased as opposed to decreasing and stable levels in B-cell-depleted patients, respectively. Control patients required increased doses of vasopressor compared to decreasing doses in B-cell depleted patients subsequent to CPT. PO2 /FiO2 decrease was more pronounced and respiratory deterioration required postinterventional extracorporeal membrane oxygenation in two control patients. Transpulmonary thermodilution revealed a further increase of the Extravascular Lung Water Index upon CPT in control patients. Conclusion: Use of CP in late stages of life-threatening COVID-19 should be used with caution but may be beneficial in B-cell-depleted patients. Further studies are necessary to assess factors predicting potential therapeutic benefits as well as possible hazards.